Pengaruh Media Sosial Instagram dan WhatsApp Terhadap Pembentukan Budaya “Alone Together” - Gunawan Saleh; Ribka Pitriani (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2018)
Social media is now highly favored by many and considered quite effective by the people of Indonesia. One example taken in this study is the social media Instagram and WhatsApp, as social media is considered to affect the forms of activity and its behavior. This study aims to investigate the influence of social media Instagram and WhatsApp against the cultural establishment